Apontamentos sobre as relações de produção na pornografia feminista - Brandão, Kelly Cipriano Sousa (2022)
The present research proposes a reflection on the emergence of a "new way" of producing pornography, classified as feminist or alternative pornography, which appears within the pornographic industry as a strategy of action and dispute for new consumer audiences. With the contribution of dialectical historical materialism, we seek to investigate the hidden relations of production in the pornographic industry, in order to find elements that allow a comparison between the pornography conventionally produced by it, and the pornography that claims to be an alternative to this production. The categories merchandise, productive work, workforce, more value and salaried work helped to understand the data obtained with the analysis of content related to the theme, and in interviews with three people who work, or have worked in the production process of feminist pornography/ alternatives. We seek to tension the debate raised by the reference bibliography on the subject, with the intention of questioning the social production of desires and needs that justify pornographic production under which the industry also instrumentalizes the production of specific consumers for specific products. Given the lack of official information on labor relations established in the pornographic industry as a whole, the management of the data obtained demanded an understanding of the legal processes that protect the activity carried out by this market in Brazil. Fundamentally, the research presented results that allow us to infer similarities and differences between the two supposedly contradictory forms of pornographic production, with regard to the production of the desire that drives consumption and the specific consumer that will effect the production of these goods, as well as the forms of extracting more value from the historically marginalized sex workforce.